Gloucester: The Wotton Cemetery Excavations, 2002. (13th August 2014) - Ellis, P.; King, R.
Abstract The report summarises results from an excavation site within the Wotton cemetery on the outskirts of Gloucester. A total of 20 cremations and 54 inhumations were excavated and are the subject of a detailed human bone report. The earliest cremation urns were of pre-Flavian date and could be paralleled by pots from the Kingsholm fortress. Cremation rite continued into the early second century, but was then replaced by inhumation burials. These dated from the later first/early second century till the fourth century. Part of a ditched enclosure, perhaps with an earlier precursor, was laid out in the second century and survived, respected by burials, into the later Roman period. The layout of this part of the Wotton cemetery is not in the orderly rows expected for urban burial in the province and this circumstance is compared both with other urban cemeteries and with practices known on rural sites. Analysis of the human bone suggested working people were buried in this part of the cemetery. At least one of the burials seems likely to have been a soldier and another may have been a person of importance very late in the life of the town.